Diopside-magnetite; A novel nanocomposite for hyperthermia applications. (January 2018) - Abdellahi, Majid; Karamian, Ebrahim; Najafinezhad, Aliakbar; Ranjabar, Fatemah; Chami, Akbar; Khandan, Amirsalar
Abstract: In the present work, the releasing heat, scaffold apatite formation, and magnetic behavior of a novel diopside-magnetite nanocomposite with various contents of magnetite (Fe3 O4 ) were evaluated. The N´eel and Brown relaxations did not have a significant effect on the specific absorption rate (SAR) of the composite samples. Indeed, magnetic saturation, M s, indicated a crucial effect on the heat release of the samples. The sample with 30 wt% magnetite had the highest value of SAR, while the sample with 20 wt% magnetite, in the form of scaffold, allowed the high amount of apatite formation on its surface. Highlights: Diopside-magnetite powders had an agglomeration trend and their coercivity was near the zero. This agglomeration was because of the permanent magnetic moment of the single domain nanoparticles. The magnetic energy was transformed to the heat by which the tendency to agglomeration increased. N´eel and Brown effects could not to describe the difference between the SAR of samples.